2007
DOI: 10.1186/cc6202
|View full text |Cite
|
Sign up to set email alerts
|

Induction of procalcitonin in liver transplant patients treated with anti-thymocyte globulin

Abstract: Introduction The aim of this study was to compare the early postoperative kinetics of procalcitonin (PCT) and C-reactive protein (CRP) serum levels in patients undergoing orthotopic liver transplantation (OLTx) with different immunosuppressive regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 17 publications
6
30
0
Order By: Relevance
“…Cardiac arrest and infection in the donor seem to be associated with high post-OLT PCT levels in the recipient. As underlined before a major limitation as far as the diagnostic accuracy of PCT is concerned stated Zazula et al, who reported the ATG-stimulated elevation of PCT [53]. This aspect was not a limitation of our research, as we prefer ATG-free immunsuppressive regimens.…”
Section: Interpretation Of Our Findingsmentioning
confidence: 76%
See 4 more Smart Citations
“…Cardiac arrest and infection in the donor seem to be associated with high post-OLT PCT levels in the recipient. As underlined before a major limitation as far as the diagnostic accuracy of PCT is concerned stated Zazula et al, who reported the ATG-stimulated elevation of PCT [53]. This aspect was not a limitation of our research, as we prefer ATG-free immunsuppressive regimens.…”
Section: Interpretation Of Our Findingsmentioning
confidence: 76%
“…In adults and children, infection and sepsis have been found to be associated with increased serum levels of calcitonin precursors [46][47][48][49][50][51][52][53]. These concentrations were shown to be positively correlated with a subsequent mortality rate [45].…”
Section: Procalcitonin; Backgroundmentioning
confidence: 99%
See 3 more Smart Citations